2017
DOI: 10.32582/aa.58.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Recent records of swordfish attacks on harpoon vessels in the Sicilian waters (Mediterranean Sea)

Abstract: Recent cases of swordfish attacks on harpoon fishing vessels of the Sicilian fleet were examined and the particular behavior adopted by this fish during the approach to fishermen was described.The information was collected in the period between 1999 and 2014 in Sicilian waters (Mediterranean Sea) through interviews with harpoon fishermen and through direct observations during research activities. Additional cases of the attacks from the previous years are also reported. Overall, 29 cases of swordfish aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…higher swordfish belligerency during the reproduction period is well documented (Romeo et al, 2017). In particular, males (smaller in size) strenuously defend females during the reproductive period, also attacking fishing boats if disturbed (Romeo et al, 2017). The shark may have disturbed a couple during their courtship and therefore was impaled by defensive reaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…higher swordfish belligerency during the reproduction period is well documented (Romeo et al, 2017). In particular, males (smaller in size) strenuously defend females during the reproductive period, also attacking fishing boats if disturbed (Romeo et al, 2017). The shark may have disturbed a couple during their courtship and therefore was impaled by defensive reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the swordfish attacks were carried out by two young individuals at different times and, in this case, we imagine that the injury provoked by the smaller bill fragment should be referred to as a first, not lethal attack. Occasional disturbance during swordfish reproductive period : higher swordfish belligerency during the reproduction period is well documented (Romeo et al ., 2017). In particular, males (smaller in size) strenuously defend females during the reproductive period, also attacking fishing boats if disturbed (Romeo et al ., 2017). The shark may have disturbed a couple during their courtship and therefore was impaled by defensive reaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clearest evidence of aggressive behaviour comes from cases involving humans, particularly when swordfish are provoked or disturbed (Georgiadou et al 2010, and references therein;Romeo et al 2017, and references therein), which has sometimes resulted in fatal spearing (Gooi et al 2006). Descriptions of some of the events indicate that swordfish usually try to pierce its 'enemy' with the bill (Romeo et al 2017). -Suay et al (2017) recently reported the case of a blue shark (Prionace glauca L.) apparently killed by a swordfish.…”
Section: Introductionmentioning
confidence: 99%